Edge concealment in a combined surface mesh and scalar-field tissue model for surgical simulations. (February 2014) - Ruthenbeck, Greg S; Reynolds, Karen J
This article describes a new approach for producing highly realistic visualizations that are interactively cuttable by utilizing the programmability of the graphics rendering pipeline. It combines interactively changing scalar-field derived mesh geometry with static mesh geometry that contains additional lighting terms created offline using three-dimensional modeling software packages. This improves visual realism of surgical simulations whilst enabling more efficient surface representations for interactive areas of the same model, in this case the newly formed surface created when interactively cutting a model. The boundary between the interactively cut surface (generated from the scalar field), and the remaining surface triangles of the static model, is jagged and unrealistic when un-enhanced. Here we describe a method for blending the two models using a simple bleeding effect along the cut edge. This allows the cut edge and the internal cut surface to blend and thereby conceals unrealistic and distracting jagged cut edges. The bloodied edge is more realistic than an unmodified hard edge, which improves the quality of the simulation overall. Moreover, as the available processing power increases the resolution that can be achieved will increase and should allow this method to be extended for slice cutting simulation.